Research progress of photonic crystals in photocatalysis - CHU Zhao-ran; CHEN Gong; ZHAO Xue-ling; LIN Dong-hai; CHEN Cheng (Cailiao gongcheng, 2021)
Photonic crystals are dielectric structure materials with photonic band gaps which are composed of matters with different dielectric constants and arranged in space periodically. The slow photon and band gap reflection in the photonic band gap can promote the photonic capture and control the interaction between light and matter. Based on the unique optical properties and large specific surface area of photonic crystals, the photonic crystal structure is introduced into the design of semiconductor photocatalytic materials, which can effectively enhance the photocatalytic reaction activity. The preparation methods of three-dimensional photonic crystals and slow photons effect was introduced in this paper,the research progress was especially summarized in the inverse opal photonic crystal as catalysts in wastewater purification of light, hydrogen production, carbon dioxide conversion and etc,and for the challenge faced by the photonic crystal light catalyst, multilayer three-dimensional photonic crystals with different refractive index and the periodicity were put forward, in order to promote photonic crystals applications in the field of photocatalysis.